(untitled) (mathematica didactica, 2022)
As far as a problem from reality is solved by using discipline-specific possibilities, a procedure according to the experimental method within (school) mathematics can be regarded as mathematical modelling. In this paper we use scientific ways of thinking and working to describe mathematical modelling processes and present alternative focuses for the analysis of modelling processes.